2009
DOI: 10.1007/s10295-009-0664-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene cloning, characterization, and heterologous expression of levansucrase from Bacillus amyloliquefaciens

Abstract: Although levan produced by Bacillus amyloliquefaciens is known to have efficient immunostimulant property which gives 100% survival of common carp when infected with Aeromonas hydrophila, no detailed reports are available describing kinetic studies of D: -glucose production and levan formation. In this study, we cloned and characterized the enzymatic kinetics using levansucrase expressed in Escherichia coli. Optimum pH for D: -glucose production and levan formation was 6.0 and 8.0, respectively, whereas optimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 27 publications
3
28
0
2
Order By: Relevance
“…A molecular mass of 49-52 kDa has been similarly reported for LS from B. amyloliquefaciens. 13,14) The molecular weight of B. amyloliquefaciens LS falls within the range reported for other LSs from Bacillus species of 52-55 kDa 9,24,28) and for LSs from gram-negative bacteria, including Z. mobilis 29) and G. diazotrophicus, 10) varying from 48 to 58 kDa.…”
Section: )mentioning
confidence: 76%
See 2 more Smart Citations
“…A molecular mass of 49-52 kDa has been similarly reported for LS from B. amyloliquefaciens. 13,14) The molecular weight of B. amyloliquefaciens LS falls within the range reported for other LSs from Bacillus species of 52-55 kDa 9,24,28) and for LSs from gram-negative bacteria, including Z. mobilis 29) and G. diazotrophicus, 10) varying from 48 to 58 kDa.…”
Section: )mentioning
confidence: 76%
“…The overall pH activity profiles of intra-and extra-cellular LSs showed only a slight difference. Mantsala and Puntala 13) and Rairakhwada et al 14) have similarly reported an optimum pH of 6.0-6.2 for extracellular LS from B. amyloliquefaciens. The pH activity profile of B. amyloliquefaciens LSs also showed features common to those of other LSs from bacillus species with an optimum pH in the range of 6.0-6.6, 9,28,32) with the exception of LS from B. circulans which exhibited optimum activity in the pH range of 5-7.…”
Section: Effect Of Ph On the Levansucrase Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…The enzymes from Zymomonas mobilis (Sangiliyandi et al 1999) and M. laevaniformans ATCC 15953 (Park et al 2003) show maximal polymerization activity at 30°C but exhibit sucrose hydrolysis activity at 45-50°C. B. amyloliquefaciens levansucrase displays the highest activity at temperatures of 4 and 30°C for levan formation and sucrose hydrolysis, respectively (Rairakhwada et al 2010). …”
Section: Effect Of Temperaturementioning
confidence: 98%
“…Generally, levan formation increases with an increasing concentration of sucrose (Ben Ammar et al 2002;Rairakhwada et al 2010;Tian et al 2011;Waldherr et al 2008;Zhang et al 2014), and the sucrose concentration usually plays an important role in controlling the molecular weight of the products.…”
Section: Effect Of the Sucrose Concentrationmentioning
confidence: 99%